Pengembangan Keprofesian Berkelanjutan dan Kinerja Guru: Mengungkap Mekanisme Mediasi Work Engagement - lia angela; Indah Herningrum (PT PUSTAKA CENDEKIA GROUP, 2026)
Educational transformation requires teachers to continuously improve their competencies and performance to adapt to changes in curriculum, technology, and student needs. In this context, Continuing Professional Development (CPD) is a strategic instrument to strengthen teachers' professional capacity. However, previous research findings indicate that the relationship between CPD and teacher performance is not entirely consistent, particularly regarding the psychological mechanisms that bridge this influence. This study aims to analyze the influence of CPD on teacher performance, both directly and indirectly through work engagement as a mediating variable. The study used a quantitative approach with a survey design of 275 high school teachers in Sungai Penuh City and Kerinci Regency who were selected through proportional random sampling. Data were collected using a Likert-sized questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) using SmartPLS. The results showed that CPD had a positive and significant effect on work engagement and teacher performance. In addition, work engagement was proven to have a positive effect on teacher performance and partially mediated the relationship between CPD and teacher performance. These findings confirm that the success of a PKB program is determined not only by increased competency but also by teachers' performance in carrying out their professional duties. Theoretically, this research enriches the study of teacher professional management by integrating the Job Demands-Resources perspective. Practically, the research findings have implications for schools and policymakers in designing PKB programs that can sustainably improve teacher engagement and performance. Keywords: Continuous Professional Development, Work Engagement, Teacher Performance, Teachers, SEM PLS.